Fair marketing: Icelandic Whale Watching - Davies, Jack (2024)
The thesis objective is to find out how the case company can improve it's fair marketing policy to customers, while promoting fairer marketing within the whale watching industry in Iceland. The purpose of the thesis is to explore Whale Watching Akureyri, and its competitors marketing techniques to see if they are honest and fair leading to potential customers joining whale watching tours in the future. Furthermore, what kind of feelings do customers do customers experience before, and after whale watching tours. A questionnaire-based survey will be used to determine how customers feelings relate to the experience they encountered with Whale Watching Akureyri. Additionally, independent research is applied on exploring whale watching companies marketing techniques through- out Iceland and how these companies’ market to gain the customers considera- tion, and if the marketing strategy is fair. All participants in the survey used in the study attended one of Whale Watching Akureyri ́s tours in the opening two weeks in November. Based on the analysed data gathered during the survey period, a fairer marketing policy will be implemented in relation to the customers feedback with comparisons constructed be tween whale watching companies around Iceland. New fairer marketing guidelines will be initiated and communicated to whale watching companies around Iceland, with the potential to eliminate false marketing in future. Study results show that fair marketing is on the whole being used with companies around Iceland with some anomalies. The combination of studies supports the idea that feelings align with expectations therefore companies providing unrealistic expectations are susceptible to negative experience post tour. Many in- teractions begin online therefore fairness and honesty is pivotal in the progression of fair marketing in Iceland. Findings suggest that customers have a degree of expectation pre whale watching tours based on images they have seen online and on social media. Whale watching sightings have a ...